AKIBAT HUKUM DARI PEMEKARAN WILAYAH TERHADAP PENDAFTARAN HAK ATAS TANAH DI KOTA PEKANBARU - BUDI SUGIYARSO (PREMISE LAW JURNAL, 2015)
Pekanbaru is the biggst townhe capital of Riau Province. The expansion is based on Law No. 32/2004 on Regional Autonomy and on the Government Regulation No. 19/1987 on the Revision of the Territorial Borders between Pekanbaru and Kampar District. The type of the research was judicial normative and descriptive analytic. The area of expansion of Pekanbaru has to be in line with the regulation stipulated in Law No. 32/2004 on Regional Autonomy and with the Government Regulation No. 19/1987 on the Revision of Territorial Borders between Pekanbaru and Kampar District. The implementation of the area of expansion of Pekanbaru which is substracted from a part of Kapar District are Siaulu PW Subdistrict and Kampar Subdistrict in Kampar District. The legal consequence is that there is the alteration of the composition of regional authority in both of these Dati II areas. Besides that, there is also the change in land registration in the Land Office and in the Office of PPAT (Official Empowered to Draw up Land Deeds) in their areas. Keywords: Area Expansion, Registration on Land Rights in Pekanbaru